2012
DOI: 10.1111/cge.12053
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell – what to do about p.C282Y heterozygotes identified by HFE screening

Abstract: Hereditary hemochromatosis (HH) is a common preventable disorder of iron overload that can result in liver cirrhosis and reduced lifespan. Most HH is due to homozygosity for the HFE p.C282Y substitution. We conducted a study of screening for p.C282Y in high schools where p.C282Y heterozygotes (CY) individuals were informed of their genotype by letter. We studied whether these individuals understood the implications of their genotype, whether this resulted in anxiety or reduced health perception and whether cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent publication investigating whether test results for HFE C282Y heterozygosity were associated with increased patient anxiety or harm indicated that these results were being appropriately interpreted as associated with no increased risk of disease. 21 However, it is possible that the observed PT survey heterogeneity in clinical interpretations of HFE genotyping may also be reflected in clinical diagnostic laboratory test reports that go to clinicians, and some misinterpretation of results may then ensue. There may be a need for further consensus and standardization in this area.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication investigating whether test results for HFE C282Y heterozygosity were associated with increased patient anxiety or harm indicated that these results were being appropriately interpreted as associated with no increased risk of disease. 21 However, it is possible that the observed PT survey heterogeneity in clinical interpretations of HFE genotyping may also be reflected in clinical diagnostic laboratory test reports that go to clinicians, and some misinterpretation of results may then ensue. There may be a need for further consensus and standardization in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised by some authors that screening may cause psychological and social stress and can be expensive considering the relatively low prevalence and incomplete penetrance. However recent studies have shown that there are minimal psychological effects of screening [146][147][148][149]. Additionally, studies outside the United States where insurance and health care access and coverage are less of a concern have suggested that practical reasons such as lack of awareness and access to screening programs are the major reasons for non-participation in screening programs [150].…”
Section: Screening and Evaluation Of Family Membersmentioning
confidence: 99%